Stator voltage harmonics and unbalance compensation of the sensorless standalone doubly fed induction generator. Issue 5 (19th August 2014) - Iwanski, Grzegorz; Pura, Piotr; Luszczyk, Tomasz; Szypulski, Mateusz; Sykulski, Jan; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Doubly fed induction generator DFIG is widely used in wind energy conversion systems and it can operate with other primary movers. The paper is focused on the standalone operation of DFIG which may expand the area of possible applications and increase capabilities of the generation system in term of power quality. Design/methodology/approach Synthesis of the control method was preceded by analysis of mathematical model of the machine. The control method based on the negative sequence and high harmonics extraction has been developed and verified in the laboratory unit. Control of the fundamental frequency component use neither rotor speed nor position sensors. Findings The original method allows to compensate negative sequence and high harmonics of the generated voltage. At the same time, due to the active filtering capability of the grid side converter, the stator phase current shape is close to sine wave. Thus, it is seen by the machine as a linear load, what eliminate the electromagnetic torque ripples. Practical implications The system and control method can be applied in variable speed generation systems, e.g. wind turbines or diesel engines operating in the standalone mode. Originality/value Although the selective compensation of negative sequence and harmonics are known in the literature, until now the methods have been verified for the system with a rotor position sensor. Moreover, the stator current feedforward improving the transient properties, as well as results of transient states caused by the load step change, have not been proposed in publications.